Analisis Proksimat Karbon Bonggol Pisang Kepok (Musa paradisiaca L) di Kecamatan Koto Tangah sebagai Sumber Karbon untuk Material Maju - Vionisa Vionisa; Umar Kalmar Nizar (Periodic, 2023)
Actived carbon can be produced from biomass waste containing starch, lignin, cellulose, and hemicellulose as a source for advanced materials. The purpose of this research is to analyze and determine the optimum temperature of the banana hump to obtain high quality, economical, and enviromentally friendly carbon. The method used for the manufacture of carbon from banana humps is by calcining in a furnace with a temperature 250°C-450°C for 1 hour. Proximate analysis of banana hump carbon used SNI 06-3730-1995 was performed by testing ash content, vapor content, and bound carbon. Based on the result obtained, the carbon of banana humpwith a carbonization temperature variation of  250°C is the optimum reaction with an ash content value of 20,26%, a vapor conten of 1,78%, and a bound carbon content of 77,96%.